New technology validation in cassava - Lynam, John K. (International Center for Tropical Agriculture, 1979)
La Colorada, on the North Coast of Colombia, was chosen by CIAT to study new technology validation in cassava. Trials measured the productivity of improved cassava production technology under actual field conditions, defined factors limiting cassava yields that may have been overlooked in the design of technology, and provided a preliminary assessment of potential constraints on adoption of the new technology. Among the components tested were selection and treatment of stem cuttings, plant population and manual weed control. A split plot design was used since local and promising cv. can be given the same treatment. Ratings of the general eating quality of cv. CMC 40 and MEX 59 indicated that neither was of sufficient quality for human consumption and would only serve for industrial purposes. Only a partial adoption of some techniques was observed. (CIAT)